(untitled) (Homoeopathy for All, 2025)
Guillain-Barré Syndrome (GBS) is a rare but serious autoimmune disorder where the body’s immune system mistakenly attacks the peripheral nervous system. This results in inflammation of the nerves, leading to symptoms such as muscle weakness, tingling, and numbness, which may progress to paralysis in severe cases.